(untitled) (Revista Brasileira de Plantas Medicinais, 2025)
This study aimed to explore ways of organizing lay information on medicinal plants that would be specifically relevant for the selection of species with potential anticancer activity. For that matter, a combination of concepts and methods from ethnobotany and ethnopharmacology with chemotaxonomy data was used. A databases was constructed with ethnopharmacological informations about plants used for signs and symptoms frequently related to a variety of cancers associated with cancer cell lines available at the South American Anticancer Drug Development Office (SOAD). Toxic effects of known anticancer drugs reported for plants were also considered The databases has 1.430 records of use for 855 plant species. Taking into account the number of records, number of indications, number of species and degree of conformity in usage, the plant families Compositae, Leguminosae, Apocynaceae, Euphorbiaceae and Rubiaceae, contributed with the greater number of potential plant species. In order to optimize the selection, records of these families were combined with the major therapeutic indications. The species that received the highest importance scores were Bidens pilosa, Achyrocline satureoides, Artemisia absinthyum, Ambrosia tenuifolia, Arnica montana, Artemisia vulgaris, Chaptalia nutans, Spilanthes ocymifolia, Cassia alata, Croton antisyphiliticus, Echites peltala, Parahancomia amapa and Retmiphyllum schomburgkii.